THE DRAINAGE PERFORMANCE AND INFLUENCING FACTORS ACCORDING TO THE PERCEPTIONS OF CONSULTANT - I Made, Kamiana I Made (Jurnal Ilmiah Teknik Sipil; Vol 25 No 2 (2021): Jurnal Ilmiah Teknik Sipil, Vol. 25 No. 2, Juli 2021, 2022)
Drainage performance, which means flow direction of drainage channels, in the Yos Sudarso-Bukit Keminting crossroad of Palangka Raya is suspected not in directed as in general from secondary channel to primary channel. This research aims to find out the consultant's perception of the direction of drainage flow in the Yos Sudarso-Bukit Keminting crossroad of Palangka Raya and the influencing factors. The research’s stages are measuring the cross-section of the drainage channel, flow direction, and drainage discharge; testing the validity and reliability of the questionnaire; collecting the data of consultant’s perceptions; testing the data normality; analyzing the perception of drainage performance descriptively; analyzing the influencing factors to the level of drainage channel by using regression technique. The research’s result shows that the channel flow of primary drainage in Yos Sudarso III Street does not flow to the primary drainage in Bukit Keminting Street, but it flows to the secondary drainage channel in Yos Sudarso-Pasar Kuliner street and Yos Sudarso-Pasar Mini street. According to the perceptions of a consultant, the kind of drainage flow level is not classified as a good one. 76.1% levels of drainage flow are simultaneously influenced by channel dimension factor, sedimentation, the elevation of the channel bottom, side of the channel, channel network, and hydraulic structures. Partially, the significant influencing factor to the level of drainage flow is sedimentation and channel dimension. Meanwhile, the channel network; elevation of channel bottom; side of the channel; and hydraulic structures do not influence significantly in partial .